PENGARUH PEMANFAATAN CHANNEL KEJARCITA TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS X SMK TI KARTIKA CENDEKIA PURWOREJO - Afriani, Faraeza; Purwanto, Joko; Daru Santoso, Suryo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has encouraged the integration of digital learning media into classroom instruction to improve students’ critical thinking skills. This study aimed to determine the effect of the KejarCita Channel on the critical thinking skills of tenth-grade students at SMK TI Kartika Cendekia Purworejo. This research employed a quantitative approach using an experimental method with a Post-test Only Control Group Design. The sample consisted of an experimental class receiving instruction through the KejarCita Channel and a control class receiving conventional instruction. Data were collected through questionnaires and critical thinking tests and analyzed using descriptive statistics, normality tests, homogeneity tests, and the Independent Sample t-test. The results showed that the utilization of the KejarCita Channel was categorized as good, with an average percentage of 66.09%. The experimental class obtained a higher mean post-test score (19.91) than the control class (15.44). Furthermore, the hypothesis test yielded a significance value of 0.000 (p < 0.05), indicating that the KejarCita Channel had a positive and significant effect on students' critical thinking skills. Therefore, the KejarCita Channel can be used as an effective digital learning medium to support the development of critical thinking skills in Indonesian language learning.